Utility of a partially covered metal stent for salvage sealing therapy for bleeding caused by duodenal invasion of pancreatobiliary cancers: Case series - Yasunobu Yamashita; Hirofumi Yamazaki; Yuki Kawaji; Takashi Tamura; Keiichi Hatamaru; Masahiro Itonaga; Reiko Ashida; Masayuki Kitano (DEN Open)
Abstract Pancreatobiliary cancer‐related gastrointestinal bleeding caused by duodenal invasion can be a life‐threatening condition that is hard to control. It is unclear whether a covered self‐expandable metal stent (CSEMS) is useful for hemostasis of bleeding related to advanced pancreatobiliary cancer. The aim of this study was to evaluate the utility of a CSEMS for hemostasis of bleeding caused by duodenal invasion of pancreatobiliary cancer. Between January 2020 and January 2022, seven patients in whom a duodenal CSEMS was inserted to control pancreatobiliary cancer‐related bleeding were enrolled. The technical and clinical success rates with respect to hemostasis, procedure time, and adverse events were assessed. All patients were inoperable cases (six with pancreatic cancer [five, stage IV; one, stage III]; and one with gallbladder cancer [stage IV]) in whom CSEMs were inserted to treat refractory bleeding caused by cancer invasion. Hemostasis was achieved in all cases (100% [7/7]). The mean procedure time was 17 ± 7.9 min. There were no adverse events, including migration and rebleeding. No rebleeding occurred up until the time of death in any of the cases (mean follow‐up period, 73 ± 27 days). Deployment of duodenal CSEMS is a useful salvage therapy for bleeding caused by advanced pancreatobiliary cancer invasion.